Prevention of Complications in the Cardiac Intensive Care Unit: A Scientific Statement From the American Heart Association. Issue 22 (1st December 2020) - Fordyce, Christopher B.; Katz, Jason N.; Alviar, Carlos L.; Arslanian-Engoren, Cynthia; Bohula, Erin A.; Geller, Bram J.; Hollenberg, Steven M.; Jentzer, Jacob C.; Sims, Daniel B.; Washam, Jeffrey B.; van Diepen, Sean
Abstract : Contemporary cardiac intensive care units (CICUs) have an increasing prevalence of noncardiovascular comorbidities and multisystem organ dysfunction. However, little guidance exists to support the development of best-practice principles specific to the CICU. This scientific statement evaluates strategies to avoid the potentially preventable complications encountered within contemporary CICUs, focusing on those that are most applicable to the CICU environment. This scientific statement reviews evidence-based practices derived in non–CICU populations, assesses their relevance to CICU practice, and highlights key knowledge gaps warranting further investigation to attenuate patient risk. Abstract : Supplemental Digital Content is available in the text.